Safety And Health Implementation Study Work (K3) In Coal Mining Companies (Case Study: PT. XYZ) - Arafik Arafik; Restu Juniah; Mohammad Zulkarnain (Indonesian Journal of Environmental Management and Sustainability, 2019)
This study aims to analyze the implementation of occupational safety and health (K3) in the coal mining company PT XYZ, Analyze and identify the factors that influence the implementation of occupational safety and health (K3) in the mining company PT XYZ. This research is a descriptive qualitative and quantitative research approach. Primary data obtained from respondents are used as a means to obtain information or data carried out by field surveys through direct observation and interviews with respondents in the company and secondary data obtained from PT XYZ collected and compiled according to the problem of this study which was conducted in literature studies. Data were analyzed through text analysis, data interpretation. Data were analyzed using the SPSS (factor analysis) program to analyze the factors that influence the implementation of occupational safety and health in the coal mining company PT XYZ.